2012
DOI: 10.1080/02640414.2011.624538
|View full text |Cite
|
Sign up to set email alerts
|

Automatic measurement of key ski jumping phases and temporal events with a wearable system

Abstract: We propose a new method, based on inertial sensors, to automatically measure at high frequency the durations of the main phases of ski jumping (i.e. take-off release, take-off, and early flight). The kinematics of the ski jumping movement were recorded by four inertial sensors, attached to the thigh and shank of junior athletes, for 40 jumps performed during indoor conditions and 36 jumps in field conditions. An algorithm was designed to detect temporal events from the recorded signals and to estimate the dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…The Keimove TM data were sent to a laptop computer via Bluetooth † . The validity and reliability of the device to measure contact/flight times and velocity at take-off variables have been previously demonstrated (Chardonnens et al, 2012;Picerno, Camomilla, & Capranica, 2011;Requena, Requena, García, Sáez-Sáez de Villarreal, & Pääsuke, 2012).…”
Section: Methodsmentioning
confidence: 94%
“…The Keimove TM data were sent to a laptop computer via Bluetooth † . The validity and reliability of the device to measure contact/flight times and velocity at take-off variables have been previously demonstrated (Chardonnens et al, 2012;Picerno, Camomilla, & Capranica, 2011;Requena, Requena, García, Sáez-Sáez de Villarreal, & Pääsuke, 2012).…”
Section: Methodsmentioning
confidence: 94%
“…For instance, the London Summer Olympics of 2012 were scheduled during Ramadan. About 25% of the participants came from Muslim-majority countries, although it is less clear how large a proportion of these individuals observed Ramadan [16]. Those who did so would have consumed increased quantities of food and drink during the hours of darkness, largely meeting their fluid and nutrient needs [1, 2, 17].…”
Section: Overviewmentioning
confidence: 99%
“…The performance decrements associated with Ramadan observance could be explained by several factors [1, 2], including disturbances of circadian rhythms [29], hypohydration [34], altered food intake [17], sleep disturbances [29], a decrease in training [16], alterations of body composition, and fatigue [16]. In a study of 15 male elite judokas, Chaouachi et al [35] found that maximal oxygen intake and performances of the squat jump, counter movement jump, and 30-m sprints were all maintained throughout Ramadan observance; the only decrement of performance was in the mean power developed during repeated 30-s vertical jumping.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They do, however, demonstrate small but acceptable limitations (e.g. [14,35,41]). Advances in measurement systems (e.g.…”
Section: Data Processing and Statistical Analysesmentioning
confidence: 99%